A critical realist appraisal of authenticity in tourism: the case of the Sámi - De Bernardi, Cecilia (Journal of Critical Realism, 2019)
This article explores the critical realist conceptualization of authenticity through its development in tourism, especially in relation to indigenous Sámi culture. Authenticity is discussed through the often relativistic perspectives surrounding it. This paper proposes a middle ground between objective and existential views; it considers authenticity to be a compromise, and it focuses on both universal components (present in all Sámi people in the tourism context) as well as mediated components (such as characteristics differently influenced by geo-history). The role of cultural tourism labels is also discussed. The overlying objective is to conceptualize authenticity so that it produces a positive effect on the tourism operations of Sámi people. Specifically, it argues that the use of certain labels or certifications, based on the concrete universal aspects of Sámi, can be beneficial. If the Sámi themselves are involved in the creation of such labels, they need not betray the objective of respecting Sámi culture.